A revision of the Neotropical tortoise beetle genus Eurypedus Gistel 1834 (Coleoptera: Chrysomelidae) - Shin, Chulwoo (Zootaxa, 2016)
The genus Eurypedus Gistel is revised based on detailed morphological study, including examination of the mouthparts and genitalia. Besides previously known diagnostic characters, such as an oblong and laterally parallel-sided body, narrow elytral lamella, narrow prosternal process between the procoxae, and angled pronotal base, new diagnostic characters are identified: antennal notches on the ventral surface of antennomeres V–XI, a stridulatory file on the vertex, and paired projections on the ventral surface of the pronotum. The distinct stridulatory file is found only in males. The number of ridges of the stridulatory file varies between 48 and 59. Eurypedus thoni Barber (= Cassida oblonga Sturm in Thon) syn. nov. is synonymized with E. peltoides (Boheman). The remaining two species E. peltoides and E. nigrosignatus (Boheman) show distinct distributions separated by the Amazon Basin.